2021
DOI: 10.1108/ijhg-05-2021-0051
|View full text |Cite
|
Sign up to set email alerts
|

Assessing community health governance for evidence-informed decision-making: a cross-sectional study across nine districts of India

Abstract: PurposeThe authors intend to assess the village health sanitation and nutrition committees (VHSNC) on six parameters, including their formation, composition, meeting frequencies, activities, supervisory mechanisms and funds receipt and expenditures across nine districts of the three states of India.Design/methodology/approachThe cross-sectional study, conducted in the states of Uttar Pradesh (five districts), Odisha (two districts) and Rajasthan (two districts), used a quantitative research design. The communi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The 35 included articles were mainly in the United States ( n = 14) [ 16 29 ], Canada ( n = 5) [ 30 34 ], Sweden ( n = 2) [ 35 , 36 ], and in other single locations such as Australia, Brazil, Burundi, India, Kenya, and Nigeria, among others ( n = 14) [ 37 50 ]. Of those included, 16 articles were qualitative studies [ 18 , 20 , 25 , 28 , 31 36 , 44 , 45 , 47 50 ], nine were non-empirical papers [ 19 , 22 , 23 , 37 39 , 41 43 ], four were quantitative studies [ 26 , 27 , 29 , 40 ], and six were mixed methods [ 16 , 17 , 21 , 24 , 30 , 46 ]. Eleven studies reported a population of interest, which were mainly Indigenous groups [ 31 , 34 , 48 ], older adults [ 19 ], patients in patient group programmes [ 21 , 27 ], academic faculty and researchers [ 40 ], and mental health practitioners [ 16 ], among others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 35 included articles were mainly in the United States ( n = 14) [ 16 29 ], Canada ( n = 5) [ 30 34 ], Sweden ( n = 2) [ 35 , 36 ], and in other single locations such as Australia, Brazil, Burundi, India, Kenya, and Nigeria, among others ( n = 14) [ 37 50 ]. Of those included, 16 articles were qualitative studies [ 18 , 20 , 25 , 28 , 31 36 , 44 , 45 , 47 50 ], nine were non-empirical papers [ 19 , 22 , 23 , 37 39 , 41 43 ], four were quantitative studies [ 26 , 27 , 29 , 40 ], and six were mixed methods [ 16 , 17 , 21 , 24 , 30 , 46 ]. Eleven studies reported a population of interest, which were mainly Indigenous groups [ 31 , 34 , 48 ], older adults [ 19 ], patients in patient group programmes [ 21 , 27 ], academic faculty and researchers [ 40 ], and mental health practitioners [ 16 ], among others.…”
Section: Resultsmentioning
confidence: 99%
“…Several activities were focused on the establishment of new teams, committees, and networks, including the formation of a newly established team specialising in sex, gender, and vulnerable populations (GVPs) [ 30 ]. Additionally, initiatives such as The Academic Network for Sexual and Reproductive Health and Rights Policy (ANSER) [ 44 ], a PBF Communities of Practice (CoP) [ 43 ] and Village Health Sanitation and Nutrition Committees (VHSNCs) [ 46 ]. Furthermore, a Task Force on Community Preventive Services published recommendations from an investigator-led review of community-based depression [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…This issue of IJHG contains seven articles that explore or discuss different areas of health governance. Papers by Sharma et al (2022) and Zalvand et al (2022) report on ubiquitous health governance issues. While Sharma et al assess community health governance, Zalvand et al explore the problem of balancing hospital expenditure while achieving quality healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Odisha, Uttar Pradesh and Rajasthan were selected because these areas had already been identified as intervention zones in a project into maternal and child health. Sharma et al (2022) used a quantitative survey design to assess six key features of 140 VHSNCs across 9 districts. Findings indicated that similar problems existed across all districts including issues preventing the VHSNCs operating as effectively as envisioned in the original National Health Mission plans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation